Learning group activities as a contribution to community service - Khansa Salsabila Rohadatul Aisy (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
One of the problems in Arahan Kidul Village, Arahan Sub-district, Indramayu Regency, West Java Province is the lack of awareness of the surrounding potential that they can utilize as an additional source that is beneficial for community education in the village. The objectives of this joint learning program and contribution in teaching staff are 1) Educate students about the importance of science; 2) Build quality, personality, creative and innovative human resources; 3) Encourage and motivate students to be enthusiastic about learning and achieving. The method of service held in the form of joint learning activities for elementary school students and teaching activities in elementary schools. The results of the joint learning program and contribution show that students are excited and enthusiastic in participating in joint learning activities held at the post. In addition, this joint learning program can also help students who have difficulty dealing with practical questions posed in school activities. In teaching activities in elementary schools, assisted by game media, it can increase students' interest in learning.   Abstrak Salah satu permasalahan yang ada di Desa Arahan Kidul, Kecamatan Arahan, Kabupaten Indramayu, Provinsi Jawa Barat adalah kurangnya kesadaran terhadap potensi sekitar yang dapat mereka manfaatkan sebagai sumber tambahan yang bermanfaat bagi pendidikan masyarakat di desa tersebut. Tujuan dari program belajar bersama dan kontribusi dalam tenaga pengajar ini yaitu 1) Mendidik peserta didik tentang pentingnya ilmu pengetahuan; 2) Membangun sumber daya manusia yang berkualitas, berkepribadian, kreatif dan inovatif; 3) Mendorong dan memotivasi peserta didik agar semangat belajar dan berprestasi. Metode pengabdian yang diadakan berupa kegiatan belajar bersama bagi peserta didik sekolah dasar dan kegiatan mengajar di sekolah dasar. Hasil dari program belajar bersama dan kontribusi menunjukkan peserta didik bersemangat dan antusias dalam mengikuti kegiatan belajar bersama yang diadakan di posko. Selain itu, program pembelajaran bersama ini juga dapat membantu peserta didik yang kesulitan menghadapi soal-soal praktis yang diajukan dalam kegiatan sekolah. Dalam kegiatan mengajar di sekolah dasar dibantu dengan media permainan mampu meningkatkan minat peserta didik dalam pembelajaran. Kata Kunci: aktivitas pembelajaran; kelompok belajar; pengabdian kepada masyarakat